Transnational architecture and urbanism: Placing starchitecture in Singapore and Chongqing - Ponzini,Davide (2021)
Abstract The period between 1990 and 2020 witnessed an increase in transnational modes of architectural and urban design, especially with reference to prominent buildings and areas. Among these, the use of famous architectural firms has spread to globalizing cities across Europe, North America, and Asia. In many cases, spectacular buildings designed by a small set of international firms (such as Frank Gehry, Jean Nouvel, Zaha Hadid, Foster+Partners) were and still are intended to alter the fate of a city, as portrayed and promoted in “Bilbao effect” narratives. Despite the clear evidence that contradicts such oversimplified rationales, attention has been largely concentrated on generalized explanations for why urban trends occur, with limited consideration given to understanding how specific projects are planned, designed, realized, and succeed or not within their contexts. By drawing on the literature and two case studies, this paper focuses on the roles that star architecture plays in the processes of developing spectacular buildings. In the conclusions, this contribution suggests future research and decision making pay greater attention to the relations between transnational projects and the local context as well as to the urban effects of such projects rather than to focus primarily on prominent characters in the urban development play and their self-interested narratives1.